Humanesis : Sound and Technological Posthumanism. - Cecchetto, David (Posthumanities., 2013)
Humanesis critically examines central strains of posthumanism, searching out biases in the ways that human-technology coupling is explained and interrogating three approaches taken by posthumanist discourse: scientific, humanist, and organismic. David Cecchetto's investigations reveal how each perspective continues to hold on to elements of the humanist tradition that it is ostensibly mobilized against. His study frontally desublimates the previously unseen presumptions that underlie each of the three thought lines and offers incisive appraisals of the work of three prominent thinkers: Ollivier Dyens, Katherine Hayles, and Mark Hansen.